PROTOTYPE WEBSITE SELEKSI PPDB JALUR PRESTASI DAN PROSES DAFTAR ULANG - Marini, Marini; Irawadi, Syafrul; Sarwindah, Sarwindah (AMIK Mitra Gama, 2025)
School is one of the educational support facilities which has a very important function as a place to seek knowledge. PPDB is an activity for accepting new students. It is hoped that this online new student admission (PPDB) system will make the implementation of PSB more transparent, accountable and accommodating. In processing the selection for new student admissions (PPDB), usually the school still records data manually so the process is considered less effective, this also greatly affects the storage of archived data, if something undesirable happens, for example data is lost or damaged, then This important data cannot be used anymore. The aim is to build a web-based application that can help both schools and students to simplify the registration process for prospective new students and speed up the data processing process. The Fast Framework model is used to create websites. The result of this research is the PPDB Achievement Track Selection Website Prototype and Re-Registration Process.